2022
DOI: 10.1088/1748-605x/ac7307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of smart carriers based on tryptophan-functionalized magnetic nanoparticles and its application in 5-fluorouracil delivery

Abstract: Multifunctional nanocarriers, specifically for tumor targeting and traceable features, have been increasingly considered in cancer therapies. Herein, a novel targeting agent (TA), tryptophan (TRP), was proposed for the synthesis of functionalized (3-aminopropyl) triethoxysilane-iron oxide nanoparticles using two methods, creating a smart drug delivery system (DDS). In one method, two-step, glutaraldehyde (GA) as a linker, bonded TRP and amino-functionalized magnetite, and in the second method, one step, TRP bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Nanotechnology offers tremendous applications in biomedical engineering for loading therapeutic cures, specifically in cancer treatments. Thanks to their unique surface features, nanoparticles (NPs) can offer a promising platform for loading therapeutic agents in drug delivery systems [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The interaction of NPs with biological systems has offered the simultaneous possibility of targeted drug delivery, monitoring, and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology offers tremendous applications in biomedical engineering for loading therapeutic cures, specifically in cancer treatments. Thanks to their unique surface features, nanoparticles (NPs) can offer a promising platform for loading therapeutic agents in drug delivery systems [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The interaction of NPs with biological systems has offered the simultaneous possibility of targeted drug delivery, monitoring, and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Mathur et al 21 reported a tryptophan-conjugated magnetic nanoparticle targeting tumours using overexpressed LAT1 transporters and showed promising results for imaging applications. In addition, Tokmedash et al 22 synthesised a targeted drug delivery system for treating breast cancer cells by tagging tryptophan to MNPs using 3-aminopropyl triethoxysilane as the crosslinker. In general, the preparation of all these hybrid magnetic nanoparticles typically requires multiple reaction and purification steps and the use of toxic coupling agents, which could compromise the biocompatibility of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles can be exposed to a constant magnetic field, and heat is absorbed in the alternating magnetic field through electromagnetic waves 12,13 . Because of the large surface area and small size of magnetic nanoparticles, they can simply reach the lesion site 14,15 . Magnetic nanoparticles capable of conducting by external magnetic fields have a high potential as drug carriers and are therefore used to treat resistant tumors with the most negligible toxicity to healthy tissue or organs.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Because of the large surface area and small size of magnetic nanoparticles, they can simply reach the lesion site. 14,15 Magnetic nanoparticles capable of conducting by external magnetic fields have a high potential as drug carriers and are therefore used to treat resistant tumors with the most negligible toxicity to healthy tissue or organs. Iron oxide paramagnetic nanoparticles are easily synthesized, biocompatible, and exhibit paramagnetic cloud properties.…”
mentioning
confidence: 99%